NEW STRATEGY IN OA - DINGRA, PROF. RARUIN; p., DR.GEECASIS; K., DR.TUSHULER (International Journal of Multidisciplinary Research and Studies, 2021)
On November fourth and fifth 2010 a gaggle of quite 100 international investigators gathered in Atlanta for the second Osteoarthritis (OA) Biomarkers Global Initiative workshop titled “Genetics and Genomics: New Targets in OA”. The primary workshop came about in April 2009 and focused on in vitro (soluble) biomarkers whilst the third and final workshop will occur in 2012 and can specialize in imaging biomarkers. The OA Research Society International (OARSI) has organized the workshops. Additionally to OARSI, the National Institute of Arthritis, Musculoskeletal and Skin Diseases, the Arthritis Foundation, Amgen, Genzyme, the American Orthopedic Society for medical specialty, and Pfizer sponsored the second meeting. it had been clear from this meeting that experiments within the genetics, epigenetics, and genomics of OA, are yielding valuable insights into the etiology of this heterogeneous disease but that much still has to be learned. Combining genetic insights with conventional biomarkers and imaging modalities may provide scientists with the improved tools to grasp this complex disease. With those tools in hand, clinicians and the industry can develop protocols to ultimately improve patient care.